Evolution of reproduction processes in the establishment and development of a company interaction system (on the example of oil and gas industry; Advances in Computer Science Research; Vol. 51 : Information Technologies in Science, Management, Social Sphere and Medicine (ITSMSSM 2016) - Matyugina (Matugina) E. G. Eleonora Grigorievna (2016, 2016)
Title screen